Culturas de prototipado y prototipado de caretas durante la pandemia: comunicación y economización de la participación cívica en México - Uribe del Águila, Verónica (2021)
This text analyzes how makers in Mexico used prototypes in the implementation and management of supply networks for the manufacture of masks for front-line personnel during the first months of the pandemic. In conversation with information theories and feminist science and technology studies, the text maintains that these prototypes had three communicative functions: (1) organizing work in a context of social distance (Suchman et al., 2002; Valentine, 2013); (2) manage uncertainty regarding contradictory health information (Corsín Jiménez, 2014; Lindtner, 2020); and (3) articulate processes of innovation and production of market value (Beckert, 2016; Eisenhardt, 1989). This triple communicative function of the prototypes made possible the articulation of civic practices and neoliberal logics, what I call, following other authors, the economization of civic participation (Lindtner, 2020; Murphy, 2017).